Effects of Azorhizophilus paspali and Paenibacillus mucilaginosus as Biofertilizer and Determination of Nutritional Efficiency by Sensors - Attar, Azade (SPRINGER HEIDELBERG, 2018)
The benefits of nitrogen-fixing and potassium-solubilizing microorganisms in plant growth were investigated by using micro-sized ion-selective sensors developed in our laboratory. Azorhizophilus paspali (ATCC 23367) having nitrogen-fixing capability and Paenibacillus mucilaginosus (DSM 24461) having potassium-solubilizing capability were used in media. The microorganisms grown in aseptic conditions were mixed with soil and compost in order to improve plant nutrition, and samples taken from growth medium were examined for 23 days by ammonium- and potassium-selective PVC membrane sensors exhibiting almost Nernstian response. The highest nitrate release were obtained on the 14th day of inoculation in samples using A. paspali. The highest potassium release was obtained on 18th day of inoculation in samples using P. mucilaginosus. The results showed that bacterial inoculation had a more stimulating effect on assimilation of N and K in compost than in soil. In addition, the effect of microbial strains on shoot and root growth and nutrient uptake of tomato was tested in pot experiments using compost. A. paspali and P. mucilaginosus inoculation increased the shoot and root dry weight of tomato seedlings, respectively, 7-14 and 12-19% when compared with the control. The results showed that addition of the microorganisms into compost would be beneficial in plant nutrition. Application of these microorganisms as biofertilizers in barren areas will protect soil from the harmful effects of chemical fertilizers with an environmentally friendly approach.
Keywords: Microbial plant nutrition; Nitrogen fixation; Potassium-solubilizing bacteria; Sensor; Biofertilizer; NITROGEN-FIXATION; PLANT-GROWTH; BIOCONTROL; L.; Science & Technology - Other Topics